A Cu foam cathode used as a Pt–RGO catalyst matrix to improve CO2 reduction in a photoelectrocatalytic cell with a TiO2 photoanode. Issue 24 (28th June 2015) - Cheng, Jun; Zhang, Meng; Liu, Jianzhong; Zhou, Junhu; Cen, Kefa
<x xml:space="preserve">Abstract</x> A Cu foam cathode was used as a Pt–RGO catalyst matrix for CO2 reduction in a photoelectrocatalytic cell with a TiO2 nanotube photoanode.